Constructing identity where it matters: sociocultural factors influencing pre-service EFL teachers during rural teaching practicums in China - Wu, Wenjie; Ahmad,, Norhakimah Khaiessa; Noordin, Nooreen; Zhao, Mengfei (Society for Research and Knowledge Management, 2025)
As China intensified efforts to achieve educational equity and rural revitalization, increasing numbers of pre-service English as a Foreign Language (EFL) teachers undertook their teaching practicums in rural schools. These settings presented distinct sociocultural challenges and critical opportunities for professional identity construction. Guided by Wenger’s Communities of Practice (1998), Akkerman and Meijer’s dialogical identity model (2011), and Lasky’s mediated agency framework (2005), this qualitative study investigated how institutional, instructional, student-related, interpersonal, communal, and emotional factors influenced the identity construction of pre-service EFL teachers during rural practicums. Data collected through semi-structured interviews, reflective journals, and classroom observations from three pre-service teachers identified several key factors shaping their identity trajectories. These included mismatched teaching assignments, excessive administrative demands, limited instructional resources, varied student needs, emotional tensions in home–school interactions, and differing levels of engagement and inclusion within professional communities. Additional roles individual agency and emotional alignment with the teaching role were pivotal in mediating identity negotiation. Collectively, these factors contributed to an ongoing and context-sensitive process of identity disruption, negotiation, and reconstruction. The findings highlighted that teacher identity was not a fixed entity, but rather a socially embedded and dynamically evolving construct. This study enriched theoretical understandings of teacher identity formation in rural contexts and provided practical insights for enhancing teacher education programs, practicum designs, and educational policies.